Initial stage oxidation of cr in dry and wet environment at 1073 K and the significant differences of FT – IR spectra produced thereof - Kaderi, Akbar; Meskon, Shahrul Razi; Ani, Mohd Hanafi; Othman, Raihan (Trans Tech Publications, Switzerland, 2012)
Little information has been known on the initial – stage oxidation if there is water vapor involved. Cr samples of 10 mm × 10 mm × 1 mm were isothermally oxidized in dry and wet environment respectively for 86.4 ks. Compact and even surface of Cr2O3 was formed on samples oxidized in dry environment. However, the ability to form compact and even Cr2O3 was retarded in wet environment. XRD analysis on all samples shows that Cr2O3 can be formed in dry and wet environment. The IR transmission spectra for samples oxidized in dry environment, were consisting of more intense peak while samples oxidized in wet environment has more relaxed peak. Moreover the peak of samples oxidized in dry tends to be narrower, while samples oxidized in wet tend to have broader peak.